Answer :

(x - 2)(x + 1) = (x - 1) (x + 3)

LHS = (x - 2)(x + 1) = x^{2} + x - 2x - 2 = x^{2} - x - 2

RHS = (x - 1) (x + 3) = x^{2} + 3x - x - 3 = x^{2} + 2x - 3

Equating LHS and RHS

x^{2} - x - 2 = x^{2} + 2x - 3

ā - 3x + 1 = 0 which is not of the form ax^{2} + bx + c = 0

Hence it is not a quadratic equation.

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Introduction to Linear Equations in Two Variables62 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

Represent tAP- Mathematics

<span lang="EN-USAP- Mathematics